2009
DOI: 10.1007/s11605-009-1041-1
|View full text |Cite
|
Sign up to set email alerts
|

Selective Management of Patients with Acute Biliary Pancreatitis

Abstract: Presence of four or five variables significantly correlated with persistent CBD stone. Biliary evaluation by endoscopic retrograde cholangiopancreatography is suggested, as initial magnetic resonance cholangiopancreatography (MRCP) may only increase cost and delay time to intervention. In the absence of any variable, biliary evaluation by intraoperative cholangiogram may be sufficient. Decisions regarding patients with one to three variables should occur on a case-to-case basis. Initial biliary evaluation by M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…We used the same 5 quantitative variables and their cutoffs as determined by the original study to determine the score. 11 We modified the proposed treatment protocol slightly. Scores of 0 and 5 were unchanged.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the same 5 quantitative variables and their cutoffs as determined by the original study to determine the score. 11 We modified the proposed treatment protocol slightly. Scores of 0 and 5 were unchanged.…”
Section: Methodsmentioning
confidence: 99%
“…11 Using retrospective data and multivariate analysis, it determined 5 quantitative variables and their cutoffs that have a positive predictive value (PPV) for CBD stones: CBD size $ 9 mm, gamma glutamyl transferase (GGT) $ 350 U/L, alkaline phosphatase (AP) $ 250 U/L, total bilirubin (TB) $ 3 mg/ dL, and direct bilirubin (DB) $ 2 mg/dL. 11 All 5 values were determined at the time of admission. One point was given for each criterion met.…”
mentioning
confidence: 99%
“…Comparable result was observed regarding the age-gender characteristics of the current study subjects where mean age of the study subjects was 35.48 (± 14.59) and their age ranged from 20 to 63 years. Researchers found that 30-75% of all cases of acute pancreatitis were due to gallstone, more than 30% of pancreatitis cases were due to complications of heavy alcohol abuse, 25% of pancreatitis was due to hypertriglyceridaemia, 15% due to post ERCP procedure and 10-30% was idiopathic 10 . In present study it was seen that acute pancreatitis was associated with hypertriglyceridemia (19.79%), gall stone (12.5%), post ERCP (6.25%) and alcoholism (2.08%).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have tried to identify variables in patients presenting with ABP which can reliably predict CBD stones. Telem et al 17 felt that grouping significant predictors as opposed to individual values, would increase reliability of detection. They found that increased CBD size on initial ultrasound, increased alkaline phosphatase, total bilirubin, direct bilirubin, gamma glutamyl transferase significantly correlated with presence of persistent stone.…”
Section: Methodsmentioning
confidence: 99%